Sickness and the Social Brain: Love in the Time of COVID - Smith, Caroline J.; Bilbo, Staci D. (Frontiers in Psychiatry, 2021)
As a highly social species, inclusion in social networks and the presence of strong social bonds are critical to our health and wellbeing. Indeed, impaired social functioning is a component of numerous neuropsychiatric disorders including depression, anxiety, and even substance use disorder. During the current COVID-19 pandemic, our social networks are at risk of fracture and many are vulnerable to the negative consequences of social isolation. Importantly, infection itself leads to changes in social behavior as a component of “sickness behavior”. Furthermore, as in the case of COVID-19, males and females often differ in their immunological response to infection, and, therefore, in their susceptibility to negative outcomes. In this review, we discuss the many ways in which infection changes social behavior – sometimes to the benefit of the host, and in some instances for the sake of the pathogen – in species ranging from eusocial insects to humans. We also explore the neuroimmune mechanisms by which these changes in social behavior occur. Finally, we touch upon the ways in which the social environment (group living, social isolation, etc.) shapes the immune system and its ability to respond to challenge. Throughout we emphasize how males and females differ in their response to immune activation, both behaviorally and physiologically.